Interactive Digital Media Remedial Programs Improve Slow Learner Reading Comprehension Skills: Program Remedial Berbasis Media Digital Interaktif Meningkatkan Keterampilan Pemahaman Membaca Siswa yang Lambat Belajar - Eko Yulianto'; Sigit Nugroho (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Reading proficiency is essential for academic success, critical thinking development, and independent learning throughout secondary education. Specific Background Seventh-grade slow learners at SMPN 2 Long Mesangat face persistent challenges in text comprehension, reading fluency, and classroom engagement, consistently scoring far below the Minimum Learning Achievement Criteria. Knowledge Gap While traditional tutoring provides some support, previous reading interventions have lacked structured digital interactivity specifically tailored to engage secondary school slow learners within a sustained remedial framework. Aims This Classroom Action Research investigates the implementation of an interactive digital media-based remedial program to elevate reading and text comprehension skills among seventh-grade slow learner students. Results Following two instructional cycles using Canva-based digital texts and interactive exercises, average reading comprehension scores surged from a 37% baseline to 87.50% in Cycle II. Furthermore, student learning activity and overall classroom engagement escalated significantly from 39% to 89%. Novelty This study demonstrates that integrating interactive digital media within a structured, multi-cycle remedial program successfully transforms passive decoding into active, independent meaning construction for students with specific learning delays. Implications Schools should integrate interactive digital multimedia into customized remedial literacy programs, providing intensive teacher scaffolding to secure equitable academic progression and motivation for students with learning difficulties. Highlights An interactive multimedia intervention significantly elevated student classroom participation and enthusiasm. The two-cycle action research framework successfully raised literacy scores above the minimum achievement threshold. Continuous teacher scaffolding combined with digital exercises strengthened inferential thinking and retelling abilities. Keywords Remedial Program; Interactive Digital Media; Reading Comprehension; Slow Learner Students; Classroom Action Research